2021
DOI: 10.1186/s41935-021-00254-2
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation with cemental incremental lines in normal and periodontally diseased teeth using phase contrast microscope: an original research

Abstract: Background Age estimation is an important factor in forensic science for human identification. Teeth are considered to play a vital role as they resist decomposition at death unlike other tissues. This resistance and the gradual structural changes that take place throughout the life of an individual have made teeth useful indicators for age estimation. Dental cementum shows continuous apposition throughout the life of an individual. Tooth cemental annulation is a microscopic method for the dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…This agrees with the results of Alghonamy et al (2015), Swetha et al (2018), andSultana et al (2021), who found that increased age can lead to greater errors, (2004) for those above 55 years old showed greater variance from their chronological age. Also, Aggarwal et al (2008) and Gupta et al (2014) found that in lower age groups, the correlation coefficients between chronological tooth age and cementum incremental lines were stronger than in the higher age groups.…”
Section: Discussionsupporting
confidence: 91%
“…This agrees with the results of Alghonamy et al (2015), Swetha et al (2018), andSultana et al (2021), who found that increased age can lead to greater errors, (2004) for those above 55 years old showed greater variance from their chronological age. Also, Aggarwal et al (2008) and Gupta et al (2014) found that in lower age groups, the correlation coefficients between chronological tooth age and cementum incremental lines were stronger than in the higher age groups.…”
Section: Discussionsupporting
confidence: 91%
“…This allows an important possibility of extension of this methodology to dental specimens of any type, in contrast to the technique still prevailing that involves the use of single-rooted teeth only (see among others [11,15]). Our findings have been confirmed by other studies [19,30] but contradict, for example, the study by Sultana et al [32], who observed a greater difference between chronological and estimated age in specimens consisting of third molars -only three third molars were included in their sample-than in the other types of teeth examined.…”
Section: Discussionsupporting
confidence: 72%
“…Apart from cases of profound periodontal pathologies, Kagerer and Grupe [19] showed that teeth with only marginal periodontal disease yielded very satisfactory outcomes if the level of section was carefully selected. Other studies also support the slight impact of periodontal diseases on TCA counting [32,54]. No influence was observed by Wittwer-Backofen et al [12] who stated: "the accuracy of the TCA age estimation is independent of periodontal disease".…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Teeth are considered to be most resistant to decomposition as they undergo least amount of degenerative changes on exposure to environmental factors. [6]The first ever known evidence of teeth being used as an age indicator originated in England in 1837 by Edwin Saunders who after examining 1049 children stated that teeth were better indicator of age than height. [5]Other systems used for age estimation bone are development, secondary sexual characteristics, and stature and weight.…”
Section: Introductionmentioning
confidence: 99%